The Nearest Route Search for A Shoe Retail Shop Using Android-Based Dijkstra Method - Muhammad Farid Fathul Huda Pradhana; R Dimas Adityo; Mas Nurul Hamidah (Fakultas Teknik Universitas Bhayangkara, 2019)
Shoe retail store is a company engaged in the sale of shoes that are developing. Until now, shoe retail stores still rely on physical stores in their business. Because it is engaged in sales, the shoe retail store requires an information system for finding a route to the store that can facilitate prospective buyers to find the location of the shoe retail store. With the shop route search information system, it can facilitate prospective buyers who do not yet know the location of the shoe retail store to find where the store is located. From the writer's observation, there are several shoe retail shops that are not indexed on Google Maps. Therefore, the author raises the title of the final project entitled